Restoration treatments enhance tree growth and alter climatic constraints during extreme drought - Rodman, Kyle C.; Bradford, John B.; Formanack, Alicia M.; Fulé, Peter Z.; Huffman, David W.; Kolb, Thomas E.; Miller‐ter Kuile, Ana T.; Normandin, Donald P.; Ogle, Kiona; Pedersen, Rory J.; Schlaepfer, Daniel R.; Stoddard, Michael T.; et al. (Ecological applications, 2025)
The frequency and severity of drought events are predicted to increase due to anthropogenic climate change, with cascading effects across forested ecosystems. Management activities such as forest thinning and prescribed burning, which are often intended to mitigate fire hazard and restore ecosystem processes, may also help promote tree resistance to drought. However, it is unclear whether these treatments remain effective during the most severe drought conditions or whether their impacts differ across environmental gradients. We used tree‐ring data from a system of replicated, long‐term (>20 years) experiments in the southwestern United States to evaluate the effects of forest restoration treatments (i.e., evidence‐based thinning and burning) on annual growth rates (i.e., basal area increment; BAI) of ponderosa pine (Pinus ponderosa), a broadly distributed and heavily managed species in western North America. The study sites were established at the onset of the most extreme drought event in at least 1200 years and span much of the climatic niche of Rocky Mountain ponderosa pine. Across sites, tree‐level BAI increased due to treatment, where trees in treated units grew 133.1% faster than trees in paired, untreated units. Likewise, trees in treated units grew an average of 85.6% faster than their pre‐treatment baseline levels (1985 to ca. 2000), despite warm, dry conditions in the post‐treatment period (ca. 2000–2018). Variation in the local competitive environment promoted variation in BAI, and larger trees were the fastest‐growing individuals, irrespective of treatment. Tree thinning and prescribed fire altered the climatic constraints on growth, decreasing the effects of belowground moisture availability and increasing the effects of atmospheric evaporative demand over multi‐year timescales. Our results illustrate that restoration treatments can enhance tree‐level growth across sites spanning ponderosa pine's climatic niche, even during recent, extreme drought events. However, shifting climatic constraints, combined with predicted increases in evaporative demand in the southwestern United States, suggest that the beneficial effects of such treatments on tree growth may wane over the upcoming decades.